Protein arginine methyltransferase 5 is a key regulator of the MYCN oncoprotein in neuroblastoma cells. Issue 3 (15th November 2014) - Park, Ji Hyun; Szemes, Marianna; Vieira, Gabriella Cunha; Melegh, Zsombor; Malik, Sally; Heesom, Kate J.; Von Wallwitz-Freitas, Laura; Greenhough, Alexander; Brown, Keith W.; Zheng, Y. George; Catchpoole, Daniel; Deery, Michael J.; et al.
Abstract : Approximately half of poor prognosis neuroblastomas (NBs) are characterized by pathognomonic MYCN gene amplification and MYCN over‐expression. Here we present data showing that short‐interfering RNA mediated depletion of the protein arginine methyltransferase 5 (PRMT5) in cell‐lines representative of NBs with MYCN gene amplification leads to greatly impaired growth and apoptosis. Growth suppression is not apparent in the MYCN‐negative SH‐SY5Y NB cell‐line, or in two immortalized human fibroblast cell‐lines. Immunoblotting of NB cell‐lines shows that high PRMT5 expression is strongly associated with MYCN‐amplification (P < 0.004, Mann–Whitney U‐test) and immunohistochemical analysis of primary NBs reveals that whilst PRMT5 protein is ubiquitously expressed in the cytoplasm of most cells, MYCN‐amplified tumours exhibit pronounced nuclear PRMT5 staining. PRMT5 knockdown in MYCN‐overexpressing cells, including the SHEP‐21N cell‐line with inducible MYCN expression leads to a dramatic decrease in MYCN protein and MYCN‐associated cell‐death in SHEP‐21N cells. Quantitative gene expression analysis and cycloheximide chase experiments suggest that PRMT5 regulates MYCN at a post‐transcriptional level. Reciprocal co‐immunoprecipitation experiments demonstrated that endogenous PRMT5 and MYCN interact in both SK‐N‐BE(2)C and NGP cell lines. By using liquid chromatography – tandem mass spectrometry (LC‐MS/MS) analysis of immunoprecipitated MYCN protein, we identified several potential sites of arginine dimethylation on the MYCN protein. Together our studies implicate PRMT5 in a novel mode of MYCN post‐translational regulation and suggest PRMT5 plays a major role in NB tumorigenesis. Small‐molecule inhibitors of PRMT5 may therefore represent a novel therapeutic strategy for neuroblastoma and other cancers driven by the MYCN oncogene. Highlights: PRMT5 targeting siRNAs induce neuroblastoma cell apoptosis. PRMT5 expression correlates with poor prognosis neuroblastoma and MYCN amplification. MYCN protein stability is regulated by PRMT5 depletion. PRMT5 and MYCN proteins physically interact. MYCN protein is post‐translationally modified by arginine methylation.